Digital solutions in the activities of small logistics enterprises (on the example of the Sverdlovsk region) - M.V. Vlasov; A.A. Sidorov (Цифровые модели и решения)
Process digitalization is becoming such an important trend in logistics. The introduction of information technologies such as the Internet of Things, blockchain, sustainability technologies, robotization, big data analysis and artificial intelligence significantly allows to increase the efficiency of logistics companies, optimize routes and improve inventory management. However, at the level of small businesses, which play a key role in last-mile delivery, such technologies are practically not used due to their high cost and unclear payback prospects. Analysis has shown that digital solutions such as digital document management, digital signature, electronic reporting systems, monitoring and control systems, cargo search platforms and special applications are popular among microenterprises and individual entrepreneurs.